Special Modes of AC Drives Operation in the Mining Industry; E3S Web of Conferences; Vol. 15 : International Innovative Mining Symposium (in memory of Prof. Vladimir Pronoza) - Payuk L. A. Lyubov Anatoljevna; Voronina N. A. Nataljya Alekseevna; Galtseva (Gal’tseva) O. V. Olga Valerievna; Zhang Dini; Rogachev A. A. (2017, 2017)
Title screen